Elevated Foxp3/CD8 Ratio in Lung Adenocarcinoma Metastatic Lymph Nodes Resected by Transcervical Extended Mediastinal Lymphadenectomy. (2nd August 2017) - Domagala-Kulawik, Joanna; Kwiecien, Iwona; Pankowski, Juliusz; Pasieka-Lis, Monika; Wolosz, Dominika; Zielinski, Marcin
Abstract : A balance between tumor invasion and immune defence system is widely investigated. Objective . The aim of this study was to evaluate lymphocyte phenotype in lymph nodes (LNs) of patients with lung cancer in relation to the presence of metastases. Methods . We investigated 364 LNs resected by transcervical extended mediastinal lymphadenectomy (TEMLA) of 49 patients with squamous cell carcinoma (SCC) or adenocarcinoma (AD) with (A) and without metastases (B). Expression of CD4, CD8, CD25, CTLA-4, and Foxp3 was assessed by immunohistochemical staining. Results . We observed a strong nuclear staining for Foxp3 in lymphocytes and cancer cells and strong membranous/cytoplasmatic reaction for CD4 and CD8, but low for CD25 and CTLA-4. There were significantly higher proportions of CD8+ cells in AD (B) versus AD (A) LNs (80% versus 52.5%, p < 0.05 ). The Foxp3/CD8 ratio was higher in AD (A) versus AD (B) LNs (0.4 versus 0.25, p < 0.05 ). No significant differences in the cell markers expression in SCC LNs were found. Conclusion . Significant differences in lymphocyte phenotype in AD may indicate an exceptional biology of this type of lung cancer. TEMLA resected LNs may serve as valuable samples for evaluation of immune status in lung cancer patients.